Impaired B-Cell Differentiation in a Patient With STAT1 Gain-of-Function Mutation - Nemoto, Kazuki; Kawanami, Toshinori; Hoshina, Takayuki; Ishimura, Masataka; Yamasaki, Kei; Okada, Satoshi; Kanegane, Hirokazu; Yatera, Kazuhiro; Kusuhara, Koichi (Frontiers in Immunology, 2020)
Hypogammaglobulinemia is a rare complication of STAT1 gain-of-function (GOF) mutations. We report an adult patient diagnosed with hypogammaglobulinemia caused by B-cell depletion during the treatment of disseminated cryptococcosis. The patient carried the STAT1 GOF mutation (c.820C>T, p.R274W). The flow cytometric analysis of his bone marrow revealed that B-cell differentiation was blocked in the stages between pre-B1b and pre-B2 cells. On the other hand, his brother who carried the same mutation displayed normal B-cell counts, thereby indicating that the unrecognized variants in same or other gene might be associated with abnormal B-cell differentiation in the patients. In conclusion, impaired B-cell differentiation in the bone marrow can cause hypogammaglobulinemia in patients with STAT1 GOF mutations.